The Effect of Platelet-Rich Fibrin on Nasal Skin Thickness in Rhinoplasty - Gode, Sercan; Ozturk, Arin; Kısmalı, Erkan; Berber, Veysel; Turhal, Goksel (Facial Plastic Surgery, 2019)
The study hypothesized the potential positive effects of platelet-rich fibrin (PRF) in postoperative rhinoplasty patients, such as better wound healing, less dead space, and less edema. The authors assessed PRF for nasal dorsum camouflage and studied its potential effects on nasal dorsal skin in rhinoplasty. Thirty-eight patients who underwent open approach primary rhinoplasty were categorized into two groups: nasal dorsal PRF group and control group. PRF membrane was used for nasal dorsum camouflage and laid over the bony dorsum and cartilage framework of the supratip area. Skin and subcutaneous soft tissue thickness were measured by linear superficial tissue ultrasound at the pre- and postoperative first week and the third month in both groups. Mean skin thickness over the supratip area was significantly higher in the control group in the first-week control. There were no significant differences in both first-week and third-month controls' nasal dorsum mean skin thickness measurements between the two groups. Regarding PRF complications, we encountered no complications in either group, including scarring, hematoma, infection, skin discoloration, and acne. The authors present the application of PRF membrane over the bony dorsum and cartilage framework of the supratip area. They observed its positive effect on postoperative edema, especially in the early postoperative period. Long-term investigations have to be performed to evaluate its potential effect on the rhinoplasty procedure. This was a level of evidence 3 study.
Keywords: nasal dorsum camouflage; platelet-rich fibrin; rhinoplasty; skin thickness